Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.foodqual.2021.104275
|View full text |Cite
|
Sign up to set email alerts
|

Finally, the chance to eat healthily: Longitudinal study about food consumption during and after the first COVID-19 lockdown in Italy

Abstract: With the COVID-19 outbreak, structural constraints and social psychological factors changed the dietary habits of many people. This two-wave longitudinal study performed in Italy aimed to explore people’s perceptions of changes in healthy and unhealthy food consumption before and during the first lockdown and the possible persistence of such changes after its official end, as a function of the number of people cohabiting, negative emotion activation, and individual eating styles. A total of 728 Italian adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 41 publications
3
43
1
1
Order By: Relevance
“…Caso Daniela (2021) conducted a longitudinal study of food consumption during and after the first COVID-19 closure in Italy, and found that food consumption patterns before and after the closure have improved, providing interesting insights into the factors that promote healthy eating during future outbreaks. Theoretical contribution can be seen in [ 71 ]. In addition to healthy diet consumption, many aspects have fueled health awareness.…”
Section: Resultsmentioning
confidence: 99%
“…Caso Daniela (2021) conducted a longitudinal study of food consumption during and after the first COVID-19 closure in Italy, and found that food consumption patterns before and after the closure have improved, providing interesting insights into the factors that promote healthy eating during future outbreaks. Theoretical contribution can be seen in [ 71 ]. In addition to healthy diet consumption, many aspects have fueled health awareness.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly believed that lockdown is a period characterized by home-confinement and consumption of unhealthy foods, creating an obesogenic environment [13,14]. On the contrary, for many people, the increased availability of time was an opportunity to improve their eating habits, partly due to greater involvement in the kitchen [15]. Previous studies demonstrated that a lack of willpower, time constraints, and taste preferences are the main difficulties in people eating healthy [16] It is likely that the lockdowns' substantial impact on people's life induced significant improvements in several nutritional behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, food samples prepared or consumed at home increased. Given the peculiar situation due to the COVID-19 pandemic during the whole of 2020, consumers' habits have inevitably changed [16]. The harsh lockdown restrictions caused the closure of restaurants, schools and company canteens, probably leading to a decrease in cases involving this kind of service.…”
Section: Discussionmentioning
confidence: 99%